Outcomes of referrals from endodontic to orofacial pain specialists: A retrospective cohort study - Ozge Erdogan; Austin Ramsey; James M. Uyanik; Jennifer L. Gibbs; Lorel E. Burns (Wiley, 2022)
Abstract Objectives Diagnosis and treatment of non‐odontogenic pain is challenging for endodontists. The purpose of the study was to investigate the outcomes of referrals to orofacial pain specialists made for patients with suspected non‐odontogenic pain, after evaluation and/or treatment by an endodontist. Materials and Methods A retrospective review of dental records was conducted for 60 patients referred from a postgraduate endodontic clinic to an orofacial pain clinic. Patient demographics, pain history, endodontic, and orofacial pain diagnoses were collected. Number of visits, length of treatment, and treatments prescribed were recorded. For analysis of outcomes, data pertinent to resolution/persistence of symptoms and patient compliance were analyzed. Results Thirty‐five patients were included in the study. The most frequent pulpal and periapical diagnoses were previously treated (62%) and symptomatic apical periodontitis (72%), respectively. The most common orofacial pain diagnosis was temporomandibular disorder. The average time spent to diagnose and treat the pain was 17 months. Pain reduction varied and was documented for 51% of patients. Indications of non‐compliance with orofacial pain appointments and treatments were documented for 66% of patients. Conclusions Non‐odontogenic pain diagnosis and treatment are challenging. Patients may have an increased predilection for developing persistent pain after endodontic treatment and/or have an undiagnosed, chronic orofacial pain condition as a true source of their chief complaint. It may be helpful for endodontists to set expectations of typical treatment times/plans when referring patients for evaluation and treatment of non‐odontogenic pain.